1985
DOI: 10.1128/iai.50.3.922-924.1985
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the cytotoxin-hemolysin gene of Vibrio vulnificus

Abstract: Genes encoding the cytotoxin-hemolysin of Vibrio vulnificus were cloned in Escherichia coli by using the lytic cloning vector, X1059. Subcloning in plasmid pBR325 resulted in the isolation of a 3.2-kilobase DNA fragment containing the cytotoxin gene. By using this fragment as a DNA probe, homologous gene sequences were detected in all 54 V. vuInificus strains studied; homologous sequences were present in none of 96 isolates from 29 other bacterial species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 21 publications
(14 reference statements)
1
34
0
Order By: Relevance
“…All tissue culture cells were grown in Eagle's minimal essential medium (MEM) supplemented with 10% fetal calf serum and 200 mM L-glutamine at 37°C in 5% CO 2 . Cytotoxicity assays were carried out on Chinese hamster ovary cells (CHO) cells, using the procedures outlined by Guerrant et al (13) that were previously used to measure the cytolysin activity present in supernatants of V. vulnificus cultures (65). Briefly, cultures were grown overnight in BHI broth (with chloramphenicol and IPTG where appropriate) at 30°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All tissue culture cells were grown in Eagle's minimal essential medium (MEM) supplemented with 10% fetal calf serum and 200 mM L-glutamine at 37°C in 5% CO 2 . Cytotoxicity assays were carried out on Chinese hamster ovary cells (CHO) cells, using the procedures outlined by Guerrant et al (13) that were previously used to measure the cytolysin activity present in supernatants of V. vulnificus cultures (65). Briefly, cultures were grown overnight in BHI broth (with chloramphenicol and IPTG where appropriate) at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…Culture supernatants from V. vulnificus are cytotoxic to cultured epithelial cells, an activity attributed to the cytolysin, a 51-kDa protein that is hemolytic to mammalian erythrocytes. Purification and subsequent cloning and sequencing indicated that this cytotoxic and hemolytic activity was caused by the protein, designated VvhA or cytolysin, which has some homology to the V. cholerae El Tor hemolysin (12,65,68). To determine the effect of the vvpD mutation on cytoxicity, serial twofold dilutions of filtered supernatants from overnight cultures were added to monolayers of CHO cells, incubated for 6 h at 37°C, and monitored for cell rounding and destruction of the monolayer (65).…”
Section: Loss Of Vvpd Does Not Affect Serum Resistance and Encap-mentioning
confidence: 99%
See 1 more Smart Citation
“…which is unique to this species (Wright et al 1985 ;Morris et al 1987). This gene has been sequenced (Yamamoto et al 1990) and used as the basis of an oligonucleotide probe for the identification of V. vulnzjicus (Wright et al 1993).…”
Section: Vibrio Vulnzjicus Contains a Cytotoxin-haemolysin Genementioning
confidence: 99%
“…The specificity of the nested PCR proce- dure using JY-1, JY-2, JY-3 and JY-4 primers was assessed with DNAs recovered from pure cultures of the strains listed in Table 1. Previous works revealed that the vvhA gene was unique to this organism by DNA hybridization (Wright et al, 1985). However, there are regions where the nucleotide sequences of the vvhA gene and the hly gene encoding hemolysin of V. cholerae showed significant homologies (Yamamoto et al, 1990).…”
Section: Specificity Of the Nested Pcr Amplificationmentioning
confidence: 97%